Flux-surface averaged radial transport in toroidal plasmas with magnetic islands. (29th August 2018) - López-Bruna, D.; Momo, B.; Predebon, I.; López-Fraguas, A.; Auriemma, F.; Suzuki, Y.; Lorenzini, R.
Abstract: In toroidal magnetic confinement fusion research, one-dimensional (1D) transport models rely on one radial coordinate that labels nested toroidal flux surfaces. The presence of magnetic islands in the magnetic geometry does not impede making 1D transport calculations if the island regions are excluded and then, if necessary, treated separately. In this work, we show a simple way to modify the flux-surface coordinate and corresponding metric coefficients when an island region is excluded. Comparisons with the metric obtained from Poincaré plots are shown, as well as applications to two types of plasma: heliac (TJ-II, CIEMAT, Spain), where the geometrical effects alone cannot explain the experimental results when islands move throughout the minor radius; and heliotron (LHD, NIFS, Japan), where we estimate the effect of an island heat sink in flux-gradient relations.